1988
DOI: 10.1099/00221287-134-9-2551
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxicity of Bacillus thuringiensis var. israelensis Crystal Proteins in vivo and in vitro

Abstract: Bacillus thuringiensis var. israelensis crystal proteins were purified by FPLC on a Mono Q column to yield 130, 65, 28, 53, 30-35 and 25 kDa proteins. All the purified proteins killed Aedes aegypti larvae after citrate precipitation, but the 65 kDa protein was the most toxic. A precipitated mixture of 27 and 130 kDa proteins was almost as toxic as solubilized crystals. In assays against a range of insect cell lines, the activated form (25 kDa) of the 27 kDa protein was generally cytotoxic with the lowest LC50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
3

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 15 publications
5
103
3
Order By: Relevance
“…The size of the parasporal inclusion produced by the recombinant strain Bti 4Q2-81 (pBTM3) were bigger than those produced by the wild type strains of Btmed and Bti, contrasting the results of Delécluse et al (1993) who observed that the Bti 4Q2-81 recombinant strain harboring the cry4B gene produced smaller inclusions, while the Bti 4Q2-81 recombinant strain harboring the (Orduz et al 1996), contrary to the observation of Chilcott and Ellar (1988) on Bti, where they found that in this Bt subspecies the most toxic component of the crystal was the 68 kDa protein. It has been suggested that proteins of 68 and 30 kDa of Btmed have a minor role in toxicity towards C. quinquefasciatus larvae (Orduz et al 1996).…”
Section: Discussioncontrasting
confidence: 54%
“…The size of the parasporal inclusion produced by the recombinant strain Bti 4Q2-81 (pBTM3) were bigger than those produced by the wild type strains of Btmed and Bti, contrasting the results of Delécluse et al (1993) who observed that the Bti 4Q2-81 recombinant strain harboring the cry4B gene produced smaller inclusions, while the Bti 4Q2-81 recombinant strain harboring the (Orduz et al 1996), contrary to the observation of Chilcott and Ellar (1988) on Bti, where they found that in this Bt subspecies the most toxic component of the crystal was the 68 kDa protein. It has been suggested that proteins of 68 and 30 kDa of Btmed have a minor role in toxicity towards C. quinquefasciatus larvae (Orduz et al 1996).…”
Section: Discussioncontrasting
confidence: 54%
“…To some extent we attempted this in the present study by expressing in lepidopteran cells a toxin normally toxic only to mosquitoes. We might have expected some toxicity as it has been shown that the activated form of the CrylVD toxin is toxic (LCs0 94 ng/ml) to M. brassicae cells in vitro (Chilcott & Ellar, 1988), and some proteolysis of Bt occurs in cell cultures and larvae (present study and Merryweather et al, 1990). However, our present results are inconclusive with respect to the toxicity of any activated proteins that may have been released inside the cell, because the CryIVD protein crystallized into inclusions, apparently soon after synthesis, and the amount of proteolysis was minimal.…”
Section: Discussionmentioning
confidence: 99%
“…When fed to mosquito larvae, or assayed in vitro against cells of the lepidopteran, Mamestra brassicae, or cells from a variety of mosquito species, this mixture of peptides causes mosquito death or cell lysis at concentration of around 100 ~tg/ml (Chilcott & Ellar, 1988). The two most abundant peptides resulting from cleavage of the 72K Fig.…”
Section: Construct Rationalementioning
confidence: 99%
See 2 more Smart Citations